CINEMATHERAPY THROUGH K-DRAMA DURING THE EARLY PERIOD OF COVID-19 PANDEMIC IN INDONESIA - Ranny Rastati (Jurnal Vokasi Indonesia, 2022)
This article discusses Korean drama (K-Drama) consumption as cinematherapy during the early period of the COVID-19 pandemic in Indonesia. In cinematherapy, videos and films are considered capable of providing therapeutic and healing effects to provide a stimulus for the audience. The cinematherapy concept was introduced by Linda Berg-Cross, Pamela Jennings, and Rhoda Baruch in 1990. The study uses the qualitative method with online in-depth interviews and literature study. The results showed that K-Drama is a pleasant activity to kill time during quarantine and social restrictions. K-Drama also has a potency to be a cinematherapy for female informants, releasing stress, tension, and anxiety due to the COVID-19 pandemic. However, K-Drama is just entertainment for male informants since they do not watch it very often compared to female informants. Another interesting finding is that female informants favored the thriller genre during the COVID-19 pandemic. For female informants, thriller K-Drama provides a sensation of tension and adrenaline rush to relieve anxiety from the burdens of life during the pandemic.